Endocervical miRNA-142 expression in patients with pelvic inflammatory disease positive for Chlamydia trachomatis - Aliaa Zara Allah Hussein Al-Tememy; Maysaa S. Alshukri; Asmaa Kadhim Gatea (Medical Journal of Babylon)
Abstract Background: The most common cause of sexually transmitted diseases that can lead to pelvic inflammatory disease (PID) and infertility is Chlamydia trachomatis. Chlamydial infections are characterized by multifocality and polymorphism changes. Chlamydia causes inflammation in the adult urethra and cervix with the possibility of serious complications, and can cause perinatal infections in infants. Highly conserved single-stranded noncoding RNAs called micro-RNAs (miRNAs), which control gene expression, have now been identified as significant effect in disease conditions. MiRNAs play important regulatory roles in various biological processes for example, differentiation, development, proliferation, apoptosis, cell cycle control, and metabolism. Changes in miRNA expression have been identified in many diseases, such as cardiac and autoimmune disorders, schizophrenia, and cancer. In this cross-sectional pilot investigation, samples were taken from control women who were not infected and from symptomatic women who were infected with C. trachomatis. Objectives: This work investigates the changes in the host miRNA-142 expression profile during chlamydial infection and not infected control group women Materials and Methods: The study included 200 female patients who were sampled, including endocervical swab from each female patient. Patients ranged in age from 20 to 45 years. A control group of 25 healthy ladies was also used. Chlamydia trachomatis was determined by conventional polymerase chain reaction (PCR) whereas miRNA-142 was detected by RT-qPCR. Results: All 200 collected endocervical swab specimens were diagnosed by the gynecologists as having PID. From all 200 collected endocervical swab specimens, it was found that only 22/200 (11%) were positive for C. trachomatis and the current study shows that the expression of the micro-142 gene elevated in C. trachomatis patients when compared to the control group, with the expression of the gene increasing more than 40% when compared to the control group. Conclusions: This study emphasizes the relevance of C. trachomatis infection in the female from 20 to 45 years in population of Iraq in Hilla city between February and August 2022. It also demonstrates the diversity of miRNA-142 expression involved in genital infection.